The future of globalisation: neo-fascism or the Green New Deal. (July 2019) - Harris, Jerry
Global capitalism is visibly showing up unacceptable inequalities and social contradictions. Three camps have emerged in the ruling class in response to over-accumulation, poverty, middle-class stagnation and environmental crisis: inclusive capitalism; militarised accumulation; the Green New Deal. All fractions adhere to neoliberal principles. Inclusive capitalism – neoliberalism with a nod to Keynesianism – means continued stagnation since it avoids the need for a social-democratic regulatory system. A turn to authoritarianism – the police state of twenty-first century neo-fascism, according to theorist William I. Robinson – is unlikely, though militarised accumulation is now an essential outlet for capital. Green capitalism, in which China is now the leading global investor, particularly with transnational public and private partners, neither breaks with neoliberalism, nor can potentially reverse environmental disaster. That would take social movements defining a Green New Deal for a sustainable capitalism to be an effective hegemonic bloc.